Use of input-output tables for shock assessment - Khoo, Lim Chun Kee (Nanyang Technological University, 2022)
Economic linkages between production sectors contribute to macroeconomic volatility. Such volatility could pose a threat to economic growth. Evidence suggests that volatility may, over time, result in lower levels of private investment, consumption, and productivity. There is also a significant correlation between volatility and financial crises. In addition, economic shocks happen periodically in economies though with variations in their magnitudes. Therefore, an analytical framework for shock assessment is essential for the relevant authorities to appreciate the impacts and thus be able to formulate more robust economic policies. This allows room for timely countermeasures and hopefully prevention against huge economic loss. This project adopts the Input-Output Model to study the impact of an economic shock on the supply chain, that is a decline in primary input or final demand for Singapore and Thailand. In addition, an attempt has been made to regionalise the Singapore national model to the 5 regions of Singapore using employment data. It is found that at the national level, Singapore’s construction plays a vital role in the supply chain. Furthermore, supply shocks to utilities and construction in certain regions could lead to huge economic losses as a result of stronger linkages.